2004
DOI: 10.1182/blood-2003-09-3129
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency virus uptake, turnover, and 2-phase transfer in human dendritic cells

Abstract: HIV-1 subverts antigen processing in dendritic cells (DCs) resulting in viral uptake, infection, and transfer to T cells. Although DCs bound monomeric gp120 and HIV-1 similarly, virus rarely colocalized with endolysosomal markers, unlike gp120, suggesting HIV-1 alters endolysosomal trafficking. Virus within DC intracellular compartments rapidly moved to DC-CD4 ؉ lymphocyte synapses when introduced to CD4 ؉ lymphocyte cultures.Although viral harboring and transfer from nonlysosomal compartments was transient, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
547
3
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 369 publications
(595 citation statements)
references
References 51 publications
(100 reference statements)
35
547
3
3
Order By: Relevance
“…[17][18][19] Recent studies have indicated that HIV-1 may be more effectively transmitted during antigen presentation between CD4 + T cells and HIV-1 exposed or infected dendritic cells (DCs), termed an infectious immunological synapse, thus providing a means for increased local viral levels. [20][21][22][23][24] As it may be impossible to protect all susceptible cells in an individual through gene delivery, the delivered protection must function to allow a limited number of primary T cells to survive, enrich, and function in the face of a robust, widespread HIV-1 infection mediated via free virus and cell-to-cell interaction.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Recent studies have indicated that HIV-1 may be more effectively transmitted during antigen presentation between CD4 + T cells and HIV-1 exposed or infected dendritic cells (DCs), termed an infectious immunological synapse, thus providing a means for increased local viral levels. [20][21][22][23][24] As it may be impossible to protect all susceptible cells in an individual through gene delivery, the delivered protection must function to allow a limited number of primary T cells to survive, enrich, and function in the face of a robust, widespread HIV-1 infection mediated via free virus and cell-to-cell interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Langerhans Cells (LC), which are a subtype of DC found in tissues, have increased HIV uptake after stimulation [63]. This could parallel stimulation of DC by BV CVL samples leading to an increase in the macropinocytosis of virions [64].…”
Section: Discussionmentioning
confidence: 99%
“…These data imply that immature DC and LC in contrast to their mature forms are more important in HIV-1 transmission. Viral endocytosis leads to partial acid-proteolytic degradation in the late endosome, although some virus may be retained in its infectious state for longer periods [27,28]. The captured HIV-1 can be transferred to T cells and this process is called trans-infection or first phase transfer [26].…”
Section: Subsets In Hiv-1 Transmissionmentioning
confidence: 99%
“…HIV-containing endosomes are diverted to the contact region, fuse with the cell membrane dumping their load of residual HIV into the synapse. Thus the amount of virus transferred declines over 12 h because of the endocytic degradation [28]. Conversely transfer of de novo produced virus which is also diverted to the contact region and in filopodia surrounding CD4 lymphocytes increases over 24-72 h [33].…”
Section: Subsets In Hiv-1 Transmissionmentioning
confidence: 99%
See 1 more Smart Citation